The effects of cognitive interference during the preparation and execution of the golf swing - Roberts, L. J.; Jackson, M. S.; Grundy, I. H. (International Journal of Sport and Exercise Psychology, 2021)
Significant research has demonstrated that expert sportspeople can accommodate irrelevant thought while executing a highly-rehearsed motor action. However, few studies have explored how irrelevant thought in preparation affects later performance. Accordingly, this repeated-measures experiment had skilled golfers (N = 24) hit approach shots (60-150 m) while secondary tasks interrupted their preparation or execution. The results showed that golfers largely maintained performance, but that distance control of the shortest shots deteriorated when preparation was disrupted. Cluster analysis indicated that interference to short-shot preparation elicited a similar number of cognitive mistakes (e.g. poor decision-making) and execution mistakes (e.g. poor timing). The data suggest that off-task thought during preparation can trigger a variety of errors by preventing the organisation of thought processes necessary for effective action. The study revealed a more complex relationship between off-task thought and motor skill failure than previously recognised.